2016
DOI: 10.1016/j.ihj.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of biomarkers in heart failure

Abstract: BNP and TNF-α are excellent predictors of mortality and morbidity in HF. Troponin-I and CRP have shown significance in predicting the outcome in HF. GGT, uric acid, and CK-MB play no role in predicting the severity and outcome in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…(10) A large body of evidence from clinical and experimental studies demonstrated NT-proBNP as a precise mortality and morbidity predictor for HF. (29,30) Although PSP levels were significantly increased in patients with HF, the results were not correlated with NT-proBNP levels in the present study.…”
Section: Discussioncontrasting
confidence: 86%
“…(10) A large body of evidence from clinical and experimental studies demonstrated NT-proBNP as a precise mortality and morbidity predictor for HF. (29,30) Although PSP levels were significantly increased in patients with HF, the results were not correlated with NT-proBNP levels in the present study.…”
Section: Discussioncontrasting
confidence: 86%
“…For myocardial zymography, lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine transaminase (ALT), serum creatine kinase isozyme (CK-MB), and hydroxybutyrate Dehydrogenase (HDBH) are the most studied myocardial zymography indicators in the clinic. The increased level of a single indicator has no strong directivity toward myocardial injury, but increased levels of multiple indicators can be used to accurately determine the severity of the injury and the effectiveness of clinical treatment [17,18,19]. Myocardial enzyme and protein levels in peripheral blood can reflect the degree of myocardial ischemic necrosis, and may provide clues for the search for NP-induced MF.…”
Section: Introductionmentioning
confidence: 99%
“…A small prospective study from India investigated the correlations between cardiac biomarkers (including B-type natriuretic peptide, Tn-I, TNF-α, and CK-MB) and the prognosis in 60 heart failure patients diagnosed according to the Framingham criteria 26 . The results showed that B-type natriuretic peptide had excellent predictive value while CK-MB played no role in this population.…”
Section: Discussionmentioning
confidence: 99%